Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS): knowledge, perception, and attitude among pharmacists in Kelantan, Malaysia. - Muhammad Munzir Sidi Omar; Nur Amalina Wahida Ab Wahab; Ann Gie Ong; Nurul Izyan Mohamed Azam; Aqilah Muhammad; Siti Nor Asiah Ab Ghani (IIUM Press, International Islamic University Malaysia, 2021)
Introduction: Although pharmacists' role in the care of human immunodeficiency virus (HIV)-infected and acquired immunodeficiency syndrome (AIDS) patients is well established, studies had reported pharmacists' negative attitudes towards people living with HIV/AIDS (PLWHA), with negative impact on HIV management. This study aimed to explore pharmacists' knowledge of HIV/AIDS, perception towards the changing of treatment regimens of HIV/AIDS, attitudes towards PLWHA, and to identify factors affecting the pharmacists' attitudes towards PLWHA in the state of Kelantan, which reportedly have the third highest number of HIV/AIDS patients in Malaysia. Materials and method: A validated online 43-item questionnaire was distributed to 400 pharmacists in Kelantan. Multivariate logistic regression was performed to identify factors associated with pharmacists' negative attitude towards PLWHA.  Results: A total of 170 respondents (response rate 42%) completed the questionnaire. Respondents had knowledge on the potential causes of HIV infection [median(IQR) score=13.00(1); maximum score=14.00], and preventive measures of HIV/AIDS transmission [median(IQR) score=12.00(1); maximum score=12.00]. On decision in changing regimens, the respondents agreed on the need to change treatment regimen for HIV/AIDS when required [median(IQR) score=7.00(2); maximum score=8.00]. Up to 40.6% of respondents thought that the treatment regimen should not be switched based on cost. Two-thirds of the respondents had negative attitudes towards PLWHA (67.1%). Respondents who worked in community pharmacy reported positive attitudes towards PLWHA (Adj OR=0.125; 95%CI=0.025-0.623; p=0.011). Conclusion: Pharmacists in Kelantan had several misconceptions towards the causes of HIV/AIDS, preventive measures of HIV/AIDS transmission, and necessity in changing treatment regimen when required. Despite good disease related knowledge, most pharmacists had negative attitudes towards PLWHA, while pharmacists working in community settings presented more positive attitudes towards PLWHA.